A fractional calculus perspective of mechanical systems modeling - Barbosa, Ramiro (2002)
The area of fractional calculus (FC) goes back to the beginning of the theory of differential calculus. Nervertheless, the application of FC just emerged in the last two decades, due to the progress in the area of chaos that revealed subtle relationchips with the FC concepts. In the area of dynamical systems theory some work has been carried out but the proposed models and algorithms are still in a preliminary stage of stablishment. Having these ideas in mind, the paper discusses a FC perspective in the study of the dynamics and control of mechanical systems.